Localization of Engineered Vasculature within 3D Tissue Constructs - Landau, Shira; Guo, Shaowei; Levenberg, Shulamit (Frontiers in Bioengineering and Biotechnology, 2018)
Today, in-vitro vessel network systems frequently serve as models for investigating cellular and functional mechanisms underlying angiogenesis and vasculogenesis. Understanding the cues triggering the observed cell migration, organization and differentiation, as well as the time frame of these processes, can improve the design of engineered micro-vasculature. Here, we present first evidence of the migration of endothelial cells into the depths of the scaffold, where they formed blood vessels surrounded by extracellular matrix and supporting cells. The supporting cells presented localization-dependent phenotypes, where cells adjacent to blood vessels displayed a more mature phenotype, with smooth muscle cell characteristics, whereas cells on the scaffold surface showed a pericyte-like phenotype. Yes-associated protein (YAP), a transcription activator of genes involved in cell proliferation and tissue growth, displayed spatially dependent expression, with cells on the surface showing more nuclear YAP than cells situated deeper within the scaffold.